Associations of NICU-Specific Stressors with Postpartum Depression in a Freestanding Children's Hospital NICU - Mari, Katey E.; Hoke, Morgan K.; Darden, Niesha; Burris, Heather H. (American Journal of Perinatology, 2025)
This study aimed to measure associations of neonatal intensive care unit (NICU)-related stressors with postpartum depression (PPD) among birthing parents of infants in a large, quaternary care, urban, U.S. children's hospital NICU.We performed a cross-sectional study of parents of infants continuously hospitalized for at least the first 6 weeks of life. Participants completed the Parental Stressor Scale: NICU and Edinburgh Postnatal Depression Scale (EPDS). An EPDS score of ≥ 10 indicated a positive PPD screen. The Multidimensional Scale of Perceived Social Support assessed emotional, practical, and informational support from family, friends, and significant others. Modified Poisson regression models calculated risk ratios of PPD per interquartile range (IQR) increment of NICU stressor scores adjusted for social support, history of anxiety or depression, infant gestational age at birth, and infant age at survey completion. We also explored whether social support modified these associations.Of the 83 participants, 34 (41%) screened positive for PPD. Per IQR increment, overall NICU stressors (adjusted risk ratio [aRR]: 1.39; 95% confidence interval [CI]: 1.01–1.92) and parental role stress (aRR: 1.78; 95% CI: 1.18–2.68) were associated with higher risk of PPD in adjusted models. Social support did not modify associations of NICU stressors with PPD.PPD was common in this population of postpartum parents of infants with long hospitalizations. PPD was associated with overall NICU stressors and loss of parental role. Given the importance of maternal mental health for family wellbeing, universal PPD screening and capacity to treat PPD in freestanding children's hospital NICUs may improve maternal and child outcomes.
Keywords: NICU; postpartum depression; stress; maternal mental health; social support